1983
DOI: 10.1016/0014-5793(83)80622-x
|View full text |Cite
|
Sign up to set email alerts
|

Translation and processing of normal (PiMM) and abnormal (PiZZ) human α1‐antitrypsin

Abstract: Human liver mRNA isolated from subjects phenotyped as homozygous PiMM or PiZZ α1‐antitrypsin, was translated in a reticulocyte cell‐free system, and α1‐antitrypsin identified by immunoprecipitation. In the presence of dog pancreas membranes the translated α1‐antitrypsin appeared as a larger product. Treatment with endo‐β‐N‐glucosaminidase yielded a protein smaller than the reticulocyte translated product, presumably due to removal of the N‐terminal signal sequence by membranes and sugar residues by endo‐β‐N‐gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…However, this explanation is less likely since previous studies have indicated that the efficiency of translocation into microsomal membranes in vitro is similar for PiM and PiZ al-AT (14,48).…”
Section: Methodsmentioning
confidence: 91%
“…However, this explanation is less likely since previous studies have indicated that the efficiency of translocation into microsomal membranes in vitro is similar for PiM and PiZ al-AT (14,48).…”
Section: Methodsmentioning
confidence: 91%
“…However, 85% of the newly synthesized polypeptide appears to be blocked in the endoplasmic production pathway of the hepatocyte, at a stage just prior to final processing of its carbohydrate sidechains, and to its entry into the Golgi secretion system. Studies using mRNA isolated from normal (MM) and deficient (ZZ) livers showed both messages were equivalent in stability and in their translation and subsequent glycosylation in cell-free systems (32)(33)(34). Injection ofthe normal M and variant Z RNA into a surrogate cell, the toad oocyte, confirmed that there was equivalent initial synthesis of the two polypeptides but showed that, whereas all the M protein was secreted, only a fraction ofthe Z antitrypsin was secreted, most ofthe Z product being blocked within the oocyte at the final (high mannose) stage of processing (35)(36)(37)(38).…”
Section: Molecular Pathology Ofthe S and Z Variantsmentioning
confidence: 99%
“…It is a prototype of the serine protease inhibitor (serpin) supergene family which includes a number of other proteins that inactivate destructive enzymes by the formation of covalently stabilized complexes (reviewed in references 3 and 4). A severe deficiency of a1 AT, characterized by selective intracellular retention ofthe mutant protein (5)(6)(7)(8)(9), is associated with chronic liver disease and premature development of pulmonary emphysema. a, AT is synthesized in human liver cells and macrophages (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%